Board incentives and board independence in dynamic agency - Svetlana Katolnik; Sandra K. Kukec; Jens Robert Schöndube (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
Efficiency of the board structure is usually perceived as linked to a higher degree of monitoring. If monitoring improves performance measurement signals, on which a manager is compensated, it can be considered desirable from the manager's point of view. As a result, having a low degree of board independence (many insiders on the board) may incentivize the board to improve its monitoring technology. However, from a dynamic perspective board monitoring is not always desirable, since it can destroy the ex ante efficient trade-off between risk and incentives under the presence of renegotiation possibility. This provides predictions for an optimal board composition seen from a dynamic perspective.
Keywords: D81; G34; M41; 330; Corporate governance; Board composition; Inside directors; Board incentives